2021
DOI: 10.1099/jgv.0.001530
|View full text |Cite
|
Sign up to set email alerts
|

RNA silencing machinery contributes to inability of BSBV to establish infection in Nicotiana benthamiana: evidence from characterization of agroinfectious clones of Beet soil-borne virus

Abstract: Beet soil-borne virus (BSBV) is a sugar beet pomovirus frequently associated with Beet necrotic yellow veins virus, the causal agent of the rhizomania disease. BSBV has been detected in most of the major beet-growing regions worldwide, yet its impact on this crop remains unclear. With the aim to understand the life cycle of this virus and clarify its putative pathogenicity, agroinfectious clones have been engineered for each segment of its tripartite genome. The biological properties of these clones were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…BSBV is transmitted by the same vector and occurs in mixed infections with BNYVV (Meunier et al, 2003). Foliar symptoms on leaf tissue but no symptom development on root tissue after BSBV infection on sugar beet plants were recently reported by Mahillon et al (2021). Whether BSBV interferes with symptom expression in mixed infection with BNYVV is unknown (Biancardi & Tamada, 2016).…”
Section: Resultsmentioning
confidence: 67%
“…BSBV is transmitted by the same vector and occurs in mixed infections with BNYVV (Meunier et al, 2003). Foliar symptoms on leaf tissue but no symptom development on root tissue after BSBV infection on sugar beet plants were recently reported by Mahillon et al (2021). Whether BSBV interferes with symptom expression in mixed infection with BNYVV is unknown (Biancardi & Tamada, 2016).…”
Section: Resultsmentioning
confidence: 67%
“…Total dsRNA was extracted from infected plant material according to Mahillon et al. (2021) and was subsequently sent for high throughput sequencing on a NovaSeq 6000 platform. A complete ToBRFV genome (6386 nt; OM305070) was assembled from the obtained reads and shared 99.8% nt identity with ToBRFV‐IL (KX619418.1).…”
Section: Figurementioning
confidence: 99%
“…In addition to BNYVV and BSBMV, P. betae also transmits two viruses from the genus Pomovirus, Beet soil-borne virus (BSBV) and Beet virus Q (BVQ). Both viruses are present in mixed infection with BNYVV and at least BSBV is distributed in sugar beet fields throughout the world (Mahillon et al 2021). Members of the genus Pomovirus have a tripartite RNA genome of about 6 kbp, 3-3.5 kbp and 2-2.5 kbp in size and are organized in rod-shaped segments (Barbarossa et al 1992).…”
Section: Polymyxa Betae Keskin Associated Soil-borne Viruses Infectin...mentioning
confidence: 99%
“…Although BSBV most often occurs in mixed infection with BNYVV, the impact of BSBV infection alone was studied only a few times (McGrann et al 2009). These studies reported about leaf and root symptoms after artificial infection, but the assumption that BSBV is a mild pathogen needs to be further addressed (Kaufmann et al 1993;Mahillon et al 2021;McGrann et al 2009). The second virus belonging to the genus Pomovirus, BVQ, was considered to be a BSBV strain due to a similar host range, transmission and genome organization but was finally assigned as an independent virus species (Koenig et al 1998).…”
Section: Polymyxa Betae Keskin Associated Soil-borne Viruses Infectin...mentioning
confidence: 99%
See 1 more Smart Citation